HUBUNGAN KEKERABATAN FENETIK VARIETAS PISANG (Musa sp.) DI PULAU AMBON - Rahmayani Notanubun; Ritha L Karuwal (Program Studi Pendidikan Biologi FKIP Unpatti, 2014)
Banana is a tropical fruit that has been popular in the community, and potentially developed in Indonesia. There are many varieties of bananas that grow wild or cultivated by the community. This leads to differences in characters between each type. The differences can be seen from the appearance of plants such as pseudo-stems, leaves, flowers, and fruit. The difference is important to know the relationship of kinship between species so that can be obtained initial information in improving the genetic properties that will produce plants with new varieties are superior.This study was conducted from December 2012 to May 2013 with the research site of Ambon Island and used exploratory methods based on the banana descriptor guidelines from the International Plant Genetic Resources Institute (IPGRI, 1996). The study showed that 7 varieties were found and identified: forty-day bananas, Jawaka, Kepok, Ambon green, King, Gold and Horn with varying morphological appearance and formed 2 main clusters with close and distant kinship. Banana on the island of Ambon has the characterization so that many sources of potential diversity need to be revealed more.